HONEY BEE (Apis mellifera) BUSINESS DEVELOPMENT STRATEGY IN TUALANG DISTRICT, SIAK REGENCY (Case Study in Setia Jaya Madu) - Fanny Herika Nainggolan; Latifa Siswati; Anto Ariyanto (Indonesian Journal of Agricultural Economics, 2022)
Research Objectives : 1. Knowing the internal factors faced by the Honey Bee (Apis mellifera) business owned by Setia Jaya Madu in Tualang District, Siak Regency. 2. Knowing the external factors faced by the Honey Bee (Apis mellifera) business owned by Setia Jaya Madu in Tualang District, Siak Regency. 3. Knowing the right strategy in developing the potential of Setia Jaya Madu's Honey Bee (Apis mellifera) business in Tualang District, Siak Regency. The method used in this study is a purposive sampling method (intentional sampling), namely 1 business owner Setia Jaya Madu, 10 workers (specifically for the production department), and 9 consumers. The results showed that the internal factors were in the form of strengths and weaknesses. Its strengths are strategic business locations that are easily accessible via google maps and located on the side of the road, have labels on the packaging, the product has been listed in BPOM, honey has passed the purity test, the workforce has attended training, the availability of nectar from the base of the acacia tree leaves as raw material in production, and have regular customers. Meanwhile, the weaknesses are that it does not have a branch of business, the technology is still simple, the product packaging in large quantities does not include a business label so that it looks less attractive, and the lack of human resources in the field of marketing. External factors are in the form of opportunities and threats. The opportunity is that it can be used as a gift, the market share is still wide, there is support and guidance from the government, and a relationship with PT Arara Abadi as a company that provides raw material for nectar from the base of the acacia tree leaves. Meanwhile, the threat is that there are competitors who also have a honey bee business in the vicinity of the respondent's business location, pests (bears) attack, and production is very dependent on the weather regarding the water content in honey. The right strategy in developing the Honey Bee (Apis mellifera) business owned by Setia Jaya Madu in Tualang District, Siak Regency is the SO (Strength-Opportunities) strategy, which is to retain regular customers to increase the market and take advantage of the availability of nectar from the base of the acacia tree leaves as raw material in production obtained in collaboration with PT Arara Abadi